Bacillus paranthracis Isolate from Blood of Fatal Ebola Virus Disease Case - M. Jeremiah Matson; Sarah L. Anzick; Friederike Feldmann; Craig A. Martens; Steven K. Drake; Heinz Feldmann; Moses Massaquoi; Daniel S. Chertow; Vincent J. Munster (Pathogens, 2020)
A Bacillus paranthracis isolate was cultured from the blood of a fatal Ebola virus disease (EVD) case in Liberia and was identified by whole genome sequencing. Although B. paranthracis has only recently been described and is poorly characterized, this case may represent the bacterial co-infection of an EVD patient.